Tratamiento de las opciones Call Spread y de las primas asociadas a opciones financieras en el Impuesto a la Renta - Cores Ferradas, Roberto (2016)
In this article, the authors explain the type of treatment the Call Spread options should be given. They argue that these should be treated as a unique derivative and not as one compound by two independent elements. Likewise, they outline the premium as an inherent element in the determination of any gains or losses from the financial options that it is decided to adopt. As an important point, they claim that adopting one specific side about the treatment of the Call Spread options and the premium implies having a viewpoint about their determination in the Income Tax.